Leiomyoma of Vagina- A Case Report (Medicine Today, 2013)
A 35 years old lady came from Borobari, Gazipur was admitted in the gynae. department of TMMC Hospital with mass in the vagina for 9 months, irregular per vaginal bleeding and dyspareunia for 1 month. Examination revealed an irregular solid mass arising from the posterior vaginal wall, which was ulcerated superficially. After conservative treatment, excision biopsy was taken and histopathology report revealed leiomyoma of the vagina. The case was managed surgically alone.DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15017 Medicine Today 2012 Vol.24(2): 89-90